Developing a Project-Based Learning Module to Enhance Oral Communication Skills of Fourth Grade Students - Latif, Tya Maulia; Sudiyanto; Cumdari (Universitas Veteran Bangun Nusantara, 2026)
Oral communication is a core competency in 21st-century education; however, instructional materials in elementary schools tend to emphasize reading and writing rather than structured speaking practice. This gap highlights the need for innovative learning resources that explicitly foster students’ oral communication skills. This study aimed to develop and evaluate a Project-Based Learning (PjBL) module designed to enhance the oral communication skills of fourth-grade elementary school students. The research employed a Research and Development (R&D) approach using the ADDIE model, encompassing analysis, design, development, implementation, and evaluation stages. The participants were 30 fourth-grade students, and the developed module was validated by three experts in material, media, and language. Data were collected through validation sheets, teacher and student response questionnaires, and pretest–posttest performance assessments.The expert validation results indicated high feasibility, with scores of 95% (material), 94% (media), and 96% (language), yielding an overall average of 95%. Teacher and student responses demonstrated strong practicality (92% and 88%, respectively; average 90%). The effectiveness test revealed a significant improvement in students’ oral communication performance, with mean scores increasing from 67 (pretest) to 86 (posttest), resulting in an N-Gain of 0.65, categorized as moderately high effectiveness. These findings suggest that the developed PjBL module is feasible, practical, and effective in improving elementary students’ oral communication skills. The study contributes to the field of communication-oriented instructional design by demonstrating how structured project-based modules, supported by simple digital enhancements such as QR-linked instructional videos, can systematically integrate speaking practice into Indonesian language learning at the primary level.